(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
If the patient develops ACD, in the absence of iron deficiency, taking iron preparations is inappropriate. Treatment in this case should be aimed at stopping the chronic inflammatory process in the remodeled small intestine.